2018
DOI: 10.1111/cpr.12478
|View full text |Cite
|
Sign up to set email alerts
|

Effect of substrate stiffness on proliferation and differentiation of periodontal ligament stem cells

Abstract: Results suggested that the osteogenic differentiation of PDLSCs might be promoted by culturing them in a stiffness-dependent manner, which regulates the Notch pathway. This might provide a new method of enhancing osteogenesis in PDLSCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 48 publications
1
26
0
Order By: Relevance
“…After cells were incubated with or without tFNAs for 6, 12, 24, and 36 h, the serum‐free medium was discarded, and then freshly prepared CCK‐8 solutions were added to each well. The absorbance of the CCK‐8 solution was measured to count the cells according to manufacturer's instruction of Cell Counting Kit‐8 (CCK‐8, MCE, USA) …”
Section: Methodsmentioning
confidence: 99%
“…After cells were incubated with or without tFNAs for 6, 12, 24, and 36 h, the serum‐free medium was discarded, and then freshly prepared CCK‐8 solutions were added to each well. The absorbance of the CCK‐8 solution was measured to count the cells according to manufacturer's instruction of Cell Counting Kit‐8 (CCK‐8, MCE, USA) …”
Section: Methodsmentioning
confidence: 99%
“…Substrate stiffness, acting as a vital biomechanical factor, has been reported to modulate cellular functions in previous 7 Stem Cells International studies [18,19,38]. It has been demonstrated that MSCs favor neuronal differentiation on relatively soft substrates, whereas they undergo osteogenic differentiation as the substrate stiffness increases [14].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, another study on bone marrowderived stem cells demonstrated that low-stiffness gels promoted cell proliferation, whereas high-stiffness gels facilitated cell osteogenic differentiation [11]. The stiffness induced behavioral differences among the different kinds of reproducible cells, including dental pulp stem cells (DPSCs) and periodontal ligament stem cells (PDLSCs) within the dental area [18,19], and others such as valve interstitial cells (VICs) [20] and oral squamous cell carcinoma cells [21] have been investigated, thus bringing more significance to this parameter in tissue engineering and regenerative therapies. It has been established based on the various previous studies on mesenchymal stem cells (MSCs) that the softer substrate matrix is suitable to induce neurogenesis and adipogenesis, while stiffer matrix tended to induce myogenesis chondrogenesis and osteogenesis [14,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, YAP/TAZ also stimulates cell proliferation by controlling the expression of a broad number of cell cycle regulators, of factors involved in DNA duplication and DNA repair, and of factors involved in mitosis ( Zhao et al, 2007 ; Zanconato et al, 2015 , 2019 ). Moreover, a soft substrate is known to decrease cellular proliferation rate ( Mih et al, 2012 ; Liu et al, 2018 ). Although these cellular changes seemed to result mainly from the stiffness difference between the two models, we used a collagen and fibronectin coating to facilitate cell attachment on the leaf scaffold and we cannot exclude this did not also affect cell behavior.…”
Section: Discussionmentioning
confidence: 99%